Biometeorological conditions during hot summer days in diverse urban environments of Banja Luka (Bosnia and Herzegovina) - Milosevic, Dragan; Trbić, Goran; Savić, Stevan; Popov, Tatjana; Ivanišević, Marko; Marković, Mirjana; Ostojić, Miloš; Dunjić, Jelena; Fekete, Renata; Garić, Bojan (Geographica Pannonica, 2022)
Intensive urbanization and global warming are impacting the health and well-being of urban population. Nevertheless, urban environments with different designs will have different micro and local climate conditions. This study used data from micrometeorological measurements performed in different urban spaces (downtown, urban park, riverside) in Banja Luka, Bosnia and Herzegovina, on hot summer days in June 2021. Air temperature, relative humidity, wind speed, and globe temperature were measured and Mean Radiant Temperature (Tmrt), Psychologically Equivalent Temperature (PET), and modified Psychologically Equivalent Temperature (mPET) were calculated for each location. Results show that the downtown is the most uncomfortable area in terms of the highest Ta, Tg, Tmrt, PET, and mPET values registered at this location. The urban park is the most comfortable area with the lowest values of Tg, Tmrt, PET, and mPET. Relative humidity is the highest at the riverside and the lowest in downtown. Furthermore, riverside had lower average Ta during summer daytime compared to urban park and downtown likely due to the synergy between river cooling effect (evaporation and sensible heat transfer) and tree shade.
Keywords: urban climate; outdoor thermal comfort; heat stress; urban park; riverside; downtown